CGMP production of the radiopharmaceutical [18F]MK‐6240 for PET imaging of human neurofibrillary tangles. (23rd March 2017) - Collier, Thomas Lee; Yokell, Daniel L.; Livni, Eli; Rice, Peter A.; Celen, Sofie; Serdons, Kim; Neelamegam, Ramesh; Bormans, Guy; Harris, Dawn; Walji, Abbas; Hostetler, Eric D.; Bennacef, Idriss; et al.
Abstract : Fluorine‐18–labelled 6‐(fluoro)‐3‐(1H‐pyrrolo[2, 3‐c]pyridin‐1‐yl)isoquinolin‐5‐amine ([ 18 F]MK‐6240) is a novel potent and selective positron emission tomography (PET) radiopharmaceutical for detecting human neurofibrillary tangles, which are made up of aggregated tau protein. Herein, we report the fully automated 2‐step radiosynthesis of [ 18 F]MK‐6240 using a commercially available radiosynthesis module, GE Healthcare TRACERlab FXFN . Nucleophilic fluorination of the 5‐diBoc‐6‐nitro precursor with potassium cryptand [ 18 F]fluoride (K[ 18 F]/K222 ) was performed by conventional heating, followed by acid deprotection and semipreparative high‐performance liquid chromatography under isocratic conditions. The isolated product was diluted with formulation solution and sterile filtered under Current Good Manufacturing Practices, and quality control procedures were established to validate this radiopharmaceutical for human use. At the end of synthesis, 6.3 to 9.3 GBq (170‐250 mCi) of [ 18 F]MK‐6240 was formulated and ready for injection, in an uncorrected radiochemical yield of 7.5% ± 1.9% (relative to starting [ 18 F]fluoride) with a specific activity of 222 ± 67 GBq/μmol (6.0 ± 1.8 Ci/μmol) at the end of synthesis (90 minutes; n = 3). [ 18 F]MK‐6240 was successfully validated for human PET studies meeting all Food and Drug Administration and United States Pharmacopeia requirements for a PET radiopharmaceutical. The present method can be easily adopted for use with other radiofluorination modules for widespread clinical research use. Abstract : The fully automated 2‐step radiosynthesis of the tau PET imaging agent, fluorine‐18 labelled 6‐(fluoro)‐3‐(1H‐pyrrolo[2, 3‐c]pyridin‐1‐yl)isoquinolin‐5‐amine ([ 18 F]MK‐6240), was validated for human use using a commercially available radiosynthesis module.